ABO‐incompatible living kidney transplantation. Issue 9 (17th August 2020) - Cen, Menger; Wang, Rending; Kong, Weiwei; Deng, Hao; Lei, Wenhua; Chen, Jianghua
Abstract: ABO‐incompatible living kidney transplantation is nowadays a routine procedure to expand living donor pool. The past decades have seen the evolution of desensitization protocol and immunosuppression regimen. Despite increased bleeding events, infectious complications, and rejection episodes reported in some studies, favorable graft and patient survival rate are now achieved, regardless of various protocols among transplant centers. Several issues such as the usage of rituximab and standardization of blood group antibody titration remain to be settled. The deposition of C4d is no longer the histopathologic hallmark of antibody‐mediated rejection, which have inspired innovative strategies of peripheral molecular screening and the improvement of histological diagnosis of AMR (antibody‐mediated rejection). The better understanding of the underlying mechanism might facilitate the distinction and therapeutic schemes of AMR.